Future Orientation and Psychological Well-being: Unravelling the Dynamics in a university in Lima - Erika Jassuly Chalén Donayre; Dora Herrera; Benjamín Lira (Revista de Psicología)
Focusing on our future is often associated with well-being, benefiting both the individual and society. However, the literature suggests that this relationship is not always consistent. Moreover, while this relationship has been studied in Lima from a subjective well-being perspective, it has not yet been explored using a psychological well-being framework. This study explores this relationship using Seigner’s, Nurmi, and Poole’s ‘Future Orientation’ and Diener et. al.’s ‘Flourishing’ constructs. Using data from 445 students from a Lima university (mean age=21.80; 64.27% females) and structural equation models, our results suggest that having a sense of internal control over one’s future career (b=.29, SE=.24, p<.01), approaching one’s future career with hope (b=.27, SE=.14, p<.01), and being optimistic about the realization of future family plans (b=.27, SE=.13, p<.05) are positively related to flourishing. Implications, limitations, and future research directions are discussed.